PENGARUH LKPD BERBASIS DISCOVERY LEARNING TERHADAP KEMANDIRIAN BELAJAR MATA PELAJARAN IPAS PESERTA DIDIK KELAS V SEKOLAH DASAR - Ivo Yuniarta; Amrina Izzatika; Siti Nurjanah; Frida Destini (Jurnal Pendidikan Dasar, 2026)
The problem of this study was motivated by the low learning independence of students in the IPAS subject. The purpose of this study was to determine the effect of using Discovery Learning–based Student Worksheets (LKPD) on the learning independence of fifth-grade students. The research method used was a quasi-experimental method with a non-equivalent control group design. The population of this study consisted of all fifth-grade students of SD Negeri 02 Hajimena, while the sample comprised students of class V A and V B selected through purposive sampling technique. Data were collected using questionnaires and observations. The data were analyzed using simple linear regression analysis. The results showed that there was an effect on students learning independence in the experimental class after the implementation of Discovery Learning–based Student Worksheets. Therefore, Discovery Learning–based Student Worksheets had a positive effect on the learning independence in the IPAS subject of fifth-grade students at SD Negeri 02 Hajimena in the 2025/2026 academic year.